Antibacterial test of secondary metabolites of Rhizosphere bacterial isolates of cat whisker against Escherichia coli and Staphylococcus aureus - Septia, Evianti Dwi; Hutauruk, Rico Halim; Razoki, Razoki; Piska, Finna (Program Studi Magister Kesehatan Masyarakat Universitas Prima Indonesia, 2024)
The rhizosphere is the zone between the root surface and soil. Rhizosphere bacteria can produce metabolites that are antibacterial because they produce phytotherapeutic compounds that have the same properties as those produced by the plant. The purpose of this study was to isolate secondary metabolite compounds from the rhizosphere bacteria of cats’ whisker plants (Orthosiphon stamineus) as antibacterial agents against Escherichia coli and Staphylococcus aureus. This study began with the isolation of rhizosphere bacteria, purification, bacterial characterization, bacterial fermentation, and antibacterial tests. The results of the isolation of Orthosiphon stamineus rhizosphere bacteria obtained as many as six isolates, with each isolate coded as RKK-1, RKK-2, RKK-3, RKK-4, RKK-5, and RKK-6. The results showed that RKK-5 had an inhibition zone against Escherichia coli with a diameter of 8.5 mm. Based on these results, it can be concluded that RKK-5 has a moderate response to Escherichia coli.